Exploring molecular and cellular signaling pathways: unraveling the pathogenesis of tendinopathy - Xu, Zihan; Hou, Wenjing; Zhang, Tao; Chen, Rui; Skutella, Thomas (Journal of orthopaedic translation, 2025)
Despite the long healing duration of tendon injuries, the outcomes of repairs are frequently suboptimal, resulting in persistent pain and reduced functionality. Current clinical approaches to tendinopathy are primarily symptomatic, encompassing nonsteroidal anti-inflammatory drugs (NSAIDs), corticosteroid injections, physical therapies, surgical interventions, loading programs, and pain management. Yet, these treatments have protracted timelines and their efficacy remains uncertain. This uncertainty stems largely from an incomplete understanding of tendinopathy's pathogenesis. Unraveling the mechanisms behind tendinopathy is essential for devising novel therapeutic strategies. In this context, this review systematic reviewed more recent cellular and molecular literature in tendinopathy, in order to summarize the up-to-date advancements including the structure and composition of healthy tendons, the pathophysiological changes in tendinopathy, the molecular pathways implicated in various forms of the condition, and current effective treatment methods. This review not only aims to offer insights but also to inspire further investigation into the mechanisms and clinical management of tendinopathy. - The translational potential of this article - A deficient understanding of the molecular mechanisms hampers the advancement of therapeutic strategies and drug development. Consequently, an in-depth examination of these molecular mechanisms is essential for comprehending the etiology of tendinopathy and for devising effective clinical management strategies.